Question and Answers Forum

All Questions      Topic List

Mensuration Questions

Previous in All Question      Next in All Question      

Previous in Mensuration      Next in Mensuration      

Question Number 114447 by bemath last updated on 19/Sep/20

Commented by bemath last updated on 19/Sep/20

gave kudos all master

gavekudosallmaster

Answered by abdullahquwatan last updated on 19/Sep/20

Misalkan ED = x  Luas ΔAEC = (1/2)×9×(4−x)  CB = (√(12^2 +4^2 ))          = 4(√(10))  CE = (√(9^2 +x^2 ))          = (√(x^2 +81))  EB = (√((4−x)^2 +3^2 ))          = (√(16−8x+x^2 +9))          = (√(x^2 −8x+25))    CB = CE + EB  4(√(10)) = (√(x^2 +81)) + (√(x^2 −8x+25))  160 = x^2 +81 + 2(√((x^2 +81)(x^2 −8x+25))) + x^2 −8x+25  didapat x = 3    Luas ΔAEC  = (1/2)×9×(4−3)  = (9/2) satuan

MisalkanED=xLuasΔAEC=12×9×(4x)CB=122+42=410CE=92+x2=x2+81EB=(4x)2+32=168x+x2+9=x28x+25CB=CE+EB410=x2+81+x28x+25160=x2+81+2(x2+81)(x28x+25)+x28x+25didapatx=3LuasΔAEC=12×9×(43)=92satuan

Answered by 1549442205PVT last updated on 19/Sep/20

S_(ABDC) =(((AB+CD).AD)/2)=(((3+9).4)/2)=24  AB//CD hence ΔAEB≃ΔDEC  ⇒((BE)/(EC))=((AB)/(CD))=(3/9)=(1/3)(1)  ⇒(S_(AEB) /S_(DEC) )=((1/3))^2 =(1/9)(2)  Since S_(ACD) =S_(BCD) =m(both triangles  have common base CD and two   equal altitude from A and B to CD),  S_(AEC) =S_(BED) =x(both equal to m−S_(CDE) )  Put S_(AEB) =a, from (2)we getS_(DEC) =9a  S_(ABCD) =24=9a+a+2x=10a+2x(3)  We have (S_(AEC) /S_(AEB) )=((CE)/(EB))=3(followsfrom(1))  ⇒S_(AEC) =x=3a.Replace into (3)we get  24=10a+2.3a=16a⇒a=24/16=1.5  ⇒x=3a=4.5  Thus,S_(AEC) =4.5

SABDC=(AB+CD).AD2=(3+9).42=24AB//CDhenceΔAEBΔDECBEEC=ABCD=39=13(1)SAEBSDEC=(13)2=19(2)SinceSACD=SBCD=m(bothtriangleshavecommonbaseCDandtwoequalaltitudefromAandBtoCD),SAEC=SBED=x(bothequaltomSCDE)PutSAEB=a,from(2)wegetSDEC=9aSABCD=24=9a+a+2x=10a+2x(3)WehaveSAECSAEB=CEEB=3(followsfrom(1))SAEC=x=3a.Replaceinto(3)weget24=10a+2.3a=16aa=24/16=1.5x=3a=4.5Thus,SAEC=4.5

Answered by mr W last updated on 19/Sep/20

((AE)/(AD))=((AB)/(AB+CD))=(3/(3+9))=(1/4)  ⇒AE=(1/4)×4=1  Δ_(AEC) =((AE×CD)/2)=((1×9)/2)=4.5

AEAD=ABAB+CD=33+9=14AE=14×4=1ΔAEC=AE×CD2=1×92=4.5

Answered by Aziztisffola last updated on 19/Sep/20

((AE)/(AD−AE))=((AB)/(CD))⇒AE×CD=AB×AD−AB×AE   9AE=12−3AE⇒AE=((12)/(12))=1  ED=3  △AEC=△ACD−△CED                 =((9×4)/2)−((9×3)/2)                 =(9/2)=4.5

AEADAE=ABCDAE×CD=AB×ADAB×AE9AE=123AEAE=1212=1ED=3AEC=ACDCED=9×429×32=92=4.5

Terms of Service

Privacy Policy

Contact: info@tinkutara.com